The Application of Modal Split Using Revealed and Stated Preference Techniques: A study in Malang - Hidayat, Muhammad Nurjati (Fakultas Teknik UB, 2018)
In this study we investigate modal split and travel behaviour in Malang by conducting person trip survey in study area. The purpose is to understand respondents’ travel behaviour and their preferences in selecting mode of transport. This is carried out to understand what are respondents feel regarding their perception on mode of transportation that available to them. The data being used are Revealed Preference (RP) and Stated Preference (SP) data. The first data based on present situation of respondents (including respondents’ characteristics and daily travel information), while the second one is hypothetical scenario that has not available in present condition. These data then compared and analysed using Multinomial Logit Model (MNL).